Analisis Coal Recovery dan Coal Losses pada Rangkaian Penambangan PIT X PT. Jembayan Muarabara Kutai Kartanegara, Kalimantan Timur - Evita Endar Apriliana; Windhu Nugroho; Henny Magdalena; Shalaho Dyna Devy; Agus Winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In mining activities, there is often a discrepancy between the plan and the actual conditions in the field, this discrepancy was found after reconciliation at the end of the progress (month). From the mining activities carried out by PT. Jembayan Muarabara (JMB), coal roof floor data was obtained from the survey which was then used to find survey tonnage, model tonnage data and actual tonnage scales. Then from this data it can be used to obtain coal recovery, coal looses in coal cleaning, loading, and coal transportation. The results of the study obtained tonnage data from the survey of 26,201.50 tons, a model of 26,488.50 tons and an actual tonnage of 24,885.09 tons. From the data obtained, the coal recovery value at the research location was 94.98% with coal losses in coal cleaning activities of 4.52% or 1196.39 tons and in loading activities of 0.5% or 120.02 tons with a tonnage discrepancy between planning and actual in the field of 1603.41 tons.